Theoretical insights into the reaction mechanism and kinetics of ampicillin degradation with hydroxyl radical - Aydogdu, Seyda; Hatipoglu, Arzu (SPRINGER, 2023)
ContextAmpicillin (AMP) is a penicillin-class beta-lactam antibiotic widely used to treat infections caused by bacteria. Therefore, due to its widespread use, this antibiotic is found in wastewater, and it contains long-term risks such as toxicity to all living organisms.MethodIn this study, the degradation reaction of ampicillin with hydroxyl radical was investigated by the density functional theory (DFT) method. All the calculations were performed with B3LYP functional at 6-31G(d,p) basis set.ResultsThe thermodynamic energy values and reaction rates of all possible reaction paths were calculated. The addition of the hydroxyl radical to the carbonyl group of the beta-lactam ring is thermodynamically the most probable reaction path. The calculated overall reaction rate constant is 1.36 x 10(11) M-1 s(-1). To determine the effect of temperature on the reaction rate, rate constants were calculated for all reaction paths at five different temperatures. The subsequent reaction kinetics of the most preferred primary route was also examined, and the toxicity values of the intermediates were estimated. The acute toxicity of AMP and its degradation product were calculated using the Ecological Structure Activity Relationships (ECOSAR) software. The degradation product was found to be more toxic than AMP.
Keywords: Ampicillin; Hydroxyl radical; DFT; CPCM; Kinetic mechanism; BETA-LACTAM ANTIBIOTICS; ADVANCED OXIDATION; BY-PRODUCTS; WATER; TRANSFORMATION; ECOTOXICITY; REMOVAL; NANOPARTICLES; Biochemistry & Molecular Biology; Biophysics; Chemistry; Computer Science